Current Topics - Sayre, Geneva (The Muslim world, 1937)
Arab Chivalry The Hadramaut A Steel Bus Trailer for the Desert Good News from Iran Prison Reform in Turkey A Moslem Heroine The Cigarette as Peace-maker (?) An Open Door in Yemen Circumcision of Converts to Islam in Malabar Chinese Moslem Women Missionaries in the Honors List